Microwave assisted synthesis of disubstituted benzyltin arylformylhydrazone complexes: anticancer activity and DNA‐binding properties - Jiang, Wu‐Jiu; Zhou, Qian; Liu, Meng‐Qin; Zhang, Fu‐Xing; Kuang, Dai‐Zhi; Tan, Yu‐Xing (Applied organometallic chemistry, 2019)
Eight disubstituted benzyltin complexes, i.e., {[R(O)C=N‐N=C (Me)COO]R'2Sn(CH3OH)}n (1a and 2b), {[R(O)C=N‐N=C (Me)COO]R'2Sn(CH3OH)}2 (1b and 1d) and {[R(O)C=N‐N=C (Me)COO]R'2Sn}n (1c, 2a, 2c, and 2d) (R = C4H3O‐, C4H3S‐, p–t‐Bu‐C6H4‐ or p‐MeO‐C6H4‐; R' = o‐Cl‐C6H4CH2‐ or o‐Me‐C6H4CH2‐), were prepared from the reaction of arylformylhydrazine, pyruvic acid and disubstituted benzyltin dichloride with microwave irradiation. All complexes were characterized by FT‐IR spectroscopy, 1H, 13C and 119Sn NMR spectroscopy, HRMS, elemental analysis, X‐ray single‐crystal diffraction and TGA. The in vitro antitumour activities of all complexes were evaluated by an MTT assay against three human cancer cell lines (NCI‐H460, HepG2, and MCF7). 2b exhibited strong antitumour activity on HepG2 cells and was expected to be a suitable platform for further chemical optimization to develop as anticancer therapeutics. The DNA binding of 2b was studied by UV–visible absorption spectrometry, fluorescence competitive assays, viscosity measurements and gel electrophoresis. Molecular docking was used to predict the binding between 2b and DNA, and the results show that 2b can become embedded in the double helix of DNA and cleave DNA. Eight disubstituted benzyltin complexes have successfully prepared. Complexe 2b exhibited strong antitumour activity on HepG2 cells and was expected to be a suitable platform for further chemical optimization to develop as anticancer therapeutics.